Teaching Mental Activity of the New Generation and Basic Pedagogical Competences - Yu.V. Gromyko; M.Yu. Prosekin (Moscow State University of Psychology and Education, 2022)
The article analyzes changes in the practice of schooling associated with the transition to forced distance learning in the context of a pandemic and the ongoing digitalization of education. These changes make it possible to discover an extremely poor arsenal of pedagogical competencies in the work of a teacher in the upper grades of secondary school. The teacher of today's school is not able to acquaint students with the basic principles of the initial forms of research and project activity, ensure that students master the methods of action of these different types of activity and connect the development of these methods of action with subject-disciplinary education. At the same time, in the system of additional education, in particular, during the NTI1 Olympiad, teams of students successfully master the principles of operation of complex equipment and perform engineering tasks. These data indicate that high school students are capable of much more intensive development of design and experimental-search thinking when solving practical problems in joint activities. In order to organize the processes of mastering project and research types of activity by schoolchildren in the upper grades of secondary school using digital models, the teacher should form a new generation of teaching mental activity based on a different system of pedagogical competencies. The article proposes a generalized description of the most important pedagogical competencies that ensure the organization of activity-based education in high school.